EVALUATION OF THE RELEASE OF ASCORBIC ACID IN PROLONGED-RELEASE TABLETS BY IN VITRO DISSOLUTION TESTS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
In vitro dissolution tests are an extremely important tool in the development and quality control of drugs, making it possible to evaluate the performance or efficiency of the pharmaceutical form in releasing the active substance through the amount dissolved in the dissolution medium when the product is subjected to specific equipment. In this sense, the main objective of the present study was to evaluate the release of ascorbic acid in prolonged release commercial vitamin C tablets by dissolution tests. Ascorbic acid and drugs of two different brands were characterized using the techniques of Molecular Absorption Spectroscopy in the Region of Infrared (IR), Thermogravimetry/Derived Thermogravimetry (TG/DTG) and Differential Scanning Calorimetry (DSC). The in vitro dissolution tests were performed in a dissolver with a paddle apparatus at a temperature of 37°C (± 0.5°C), employing 900 mL of ultrapure water as the dissolution medium and a stirring speed of 50 rpm. The ascorbic acid dissolved in the aliquots of dissolution media obtained during the tests were quantified using the UV-Vis Molecular Absorption Spectroscopy technique. From the dissolution profiles, it was observed that the formulations of both brands promoted a prolonged release of ascorbic acid. The brand drug A dissolved about 67% of the active principle in about 360 minutes. The brand drug B, however, dissolved about 72% at the same dissolution time. Release kinetics was evaluated using kinetic models such as order zero, first order and Higuchi. The model that best fit the experimental data was that of Higuchi.